Ethics in health care: Confidentiality and information technologies - D. Knapp van Bogaert; G.A. Ogunbanjo (South African Family Practice)
Before the advent of the new communication and information technologies (NCITs), patient care was sometimes delayed because of the lengthy time it took to transmit patient information from a doctor in one location to a colleague in another. NCITs bring many advances to medicine, including to the area of communication. With a simple click, rural doctors can access their patients’ laboratory test results, transmit images immediately, and receive feedback from a number of specialists working far away in teaching hospital centres. Doctors have a general obligation to preserve patient confidentiality, which includes keeping patients’ information confidential. Medical confidentiality remains a vital part of ethical professional practice and it is likely that it will remain so. However, data transfer in this age of NCITs presents new ethical challenges in maintaining patient confidentiality.